Influence of oestrogen deficiency and excessive mechanical stress on condylar head of mandible. (15th July 2020) - Nogami, Shinnosuke; Yamauchi, Kensuke; Odashima, Kenji; Ito, Ko; Iikubo, Masahiro; Kumasaka, Akira; Martinez‐de la Cruz, Gerardo; Gaggl, Alexander; Kumamoto, Hiroyuki; Takahashi, Tetsu
Abstract: Objective: We assessed the aetiology of idiopathic condylar resorption by examining the effects of oestrogen and compressive mechanical stress under a low systemic oestrogen condition in temporomandibular joints (TMJ) caused by an ovariectomy. Materials and Methods: Female rabbits were divided into non‐ovariectomy (non‐OVX) and ovariectomy (OVX) groups. A cortical osteotomy was performed with a custom device that was increased in length by 0.25 mm every 12 hr for 1 week after the operation, during which the TMJs in the rabbits received compressive mechanical stress. Samples from both groups were examined with micro‐computed tomography and histological staining. Results: Area and depth of bone resorption were both greater in the OVX group. Furthermore, a significantly earlier and greater prevalence of sub‐condylar bone resorption was noted in that group, while cells positive for tartrate‐resistant acid phosphatase were increased in the OVX group. Conclusions: The present findings suggest that oestrogen induced a much greater amount of bone resorption on the anterior surface of the condylar head at an earlier stage in the TMJs of the present model rabbits. Thereafter, restoration of TMJ function appeared to occur in a normal manner.